ADVANTAGES OF GROWING PISTACHIOS IN COLMATED SOILS (Scientific journal of the Fergana State University, 2025)
The article presents the chemical composition of the pistachio plant, products made from it used in medicine and technology, as well as the advantages of growing in colmatized soils formed on light gray soils.